2017
DOI: 10.3823/2530
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, prevalence of hair smoothing products that contain formaldehyde and determinants of their harmful effects among women in Saudi Arabia

Abstract: Individuals who use hair smoothing products at home or in a salon work environment are at risk of exposure to various chemical compounds. Formaldehyde mixed with keratin as a hair straightening product is in common use by women in Saudi Arabia. The high temperatures used during blow-drying can release gas fumes that have several implications to include irritation of the skin, eyes and respiratory complications. Furthermore, formaldehyde is classified as a known human carcinogen. The aim of this study is to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Heavy metals, including Cr, Al, Cd, and Pb, which were selected for study in this paper, interact with the human body through many proteins, genes, and DNA by losing one or many electrons and manufactured metals cations, which have many affinity sites to various macromolecules, and many tissues and body organs are also affected [ 6 , 17 ]. The current results for groups 1 and 2 ( Table 2 and Table 3 ) may also be due to the daily use of other cosmetics, food, or drinks, and previous research has indicated various kinds of food contamination and toxicity, including those that are manufactured or fresh [ 14 , 15 , 23 , 25 , 26 , 32 , 33 , 34 , 35 , 36 , 37 ]. Hence, the human body’s direct exposure to heavy metals from food, beverages, cosmetics, soil, air, tobacco, dust, and skin can affect internal biological systems depending upon the dose, leading to acute early effective and chronic accumulation, consequently, leading to various macromolecule infection and health issues, including deadly neurological, brain, liver, kidney, bone, skin, and other fetal diseases [ 1 , 38 ].…”
Section: Discussionmentioning
confidence: 84%
“…Heavy metals, including Cr, Al, Cd, and Pb, which were selected for study in this paper, interact with the human body through many proteins, genes, and DNA by losing one or many electrons and manufactured metals cations, which have many affinity sites to various macromolecules, and many tissues and body organs are also affected [ 6 , 17 ]. The current results for groups 1 and 2 ( Table 2 and Table 3 ) may also be due to the daily use of other cosmetics, food, or drinks, and previous research has indicated various kinds of food contamination and toxicity, including those that are manufactured or fresh [ 14 , 15 , 23 , 25 , 26 , 32 , 33 , 34 , 35 , 36 , 37 ]. Hence, the human body’s direct exposure to heavy metals from food, beverages, cosmetics, soil, air, tobacco, dust, and skin can affect internal biological systems depending upon the dose, leading to acute early effective and chronic accumulation, consequently, leading to various macromolecule infection and health issues, including deadly neurological, brain, liver, kidney, bone, skin, and other fetal diseases [ 1 , 38 ].…”
Section: Discussionmentioning
confidence: 84%